The role of perivascular adipose tissue-secreted adipocytokines in cardiovascular disease - Cai, Meichao; Zhao, Dongsheng; Han, Xiao; Han, Shuang; Zhang, Wenxin; Zang, Zhennan; Gai, Chenchen; Rong, Rong; Gao, Tian (Frontiers in Immunology, 2023)
Perivascular adipose tissue and the vessel wall are connected through intricate bidirectional paracrine and vascular secretory signaling pathways. The secretion of inflammatory factors and oxidative products by the vessel wall in the diseased segment has the ability to influence the phenotype of perivascular adipocytes. Additionally, the secretion of adipokines by perivascular adipose tissue exacerbates the inflammatory response in the diseased vessel wall. Therefore, quantitative and qualitative studies of perivascular adipose tissue are of great value in the context of vascular inflammation and may provide a reference for the assessment of cardiovascular ischemic disease.